2014
DOI: 10.1002/cncr.28551
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of mitochondrion‐associated autophagy inhibitor LRPPRC are associated with poor prognosis in patients with prostate cancer

Abstract: BACKGROUND Autophagy has recently been found to play important roles in tumorigenesis and LRPPRC has been identified as an inhibitor that suppresses autophagy and mitophagy and maintains mitochondrial activity. We hypothesized that LRPPRC levels can be used as a biomarker for diagnosis and prognosis of prostate cancer. METHODS We performed immunochemistry analysis to evaluate the levels of LRPPRC in 112 samples collected from patients with prostate adenocarcinomas (PCa) and 38 samples from patients with beni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 49 publications
4
46
1
Order By: Relevance
“…In our study, PCa tissue from the majority of patients was obtained by biopsy, which was similar to the situation in some other studies 18 19…”
Section: Methodssupporting
confidence: 74%
“…In our study, PCa tissue from the majority of patients was obtained by biopsy, which was similar to the situation in some other studies 18 19…”
Section: Methodssupporting
confidence: 74%
“…The SAS software was used for all statistical analyses, and a P value of <0.05 was considered significant. All statistical analyses were carried out similarly as previously described (Jiang et al ., 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Oxidative stress in turn activates NLRP3 inflammasome and eventually induces an inflammatory form of cell death referred to as pyroptosis that promotes the mortality and impair the survival of host structural, hematopoietic, and immune‐competent cells (Lamkanfi & Dixit, 2014; Ryter et al ., 2014; Terlizzi et al ., 2014; Yu et al ., 2014). Cancer patients with defective autophagy live a short lifespans (Jiang et al ., 2014, 2015). Both calorie restriction and pharmacologic agents that mimic the impact of calorie restriction induce autophagy and prolong lifespans (Madeo et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] In the field of PC research as well, a few studies assessed the significance of molecular markers involved in autophagy. [15][16][17] For example, Giatromanolaki et al 17 reported that the strong and extensive expression of LC3 in PC specimens was closely associated with the Gleason score, whereas Jiang et al 16 showed the significant impact of the elevated expression of a mitochondrion-associated autophagy inhibitor, leucine-rich pentatricopeptide repeat motifecontaining protein, on the prognosis of PC patients at a late stage with a poor prognosis. To our knowledge, however, there have not been any studies investigating the prognostic impact of molecular markers involved in the autophagic pathway for men with early stage PC.…”
Section: Commentmentioning
confidence: 99%
“…8,9 In recent years, there have been several studies reporting that the expression profiles of molecular markers consisting of the autophagy pathway could be used as useful predictors of clinical courses in several types of human malignant tumor [10][11][12][13][14] ; however, limited information is available on the prognostic significance of autophagy-related proteins in patients with PC. [15][16][17] Considering these findings, we evaluated the expression patterns of multiple autophagy-related proteins, including autophagy-related gene 5 (Atg5), autophagyrelated gene 9 (Atg9), Beclin1, microtubule-associated protein light chain 3 (LC3), and UNC-51elike kinase 1 (ULK1), in RP specimens from 160 patients with localized PC to analyze the prognostic significance of these markers in this cohort of patients.…”
mentioning
confidence: 99%